Cranefly fauna (Diptera: Limoniidae, Pediciidae, Tipulidae) of the Republic of Mordovia, Russia - Valentin Pilipenko; ALEXANDER B. RUCHIN; GENNADY B. SEMISHIN (Society for Indonesian Biodiversity, 2020)
Abstract. Pilipenko VE, Ruchin AB, Semishin GB. 2020. Cranefly fauna (Diptera: Limoniidae, Pediciidae, Tipulidae) of the Republic of Mordovia, Russia. Biodiversitas 21: 355-369. The paper summarizes the Tipuloidea fauna of the Republic of Mordovia, Russia, for the first time. Among the 94 species, 29 species of Limoniidae and 14 species of Tipulidae have not been previously recorded from the region. The family Pediciidae, with five species, is also recorded for the first time. Six species are recorded from ?entral European Russia for the first time: Hexatoma (Hexatoma) fuscipennis (Curtis, 1836), Phylidorea (Phylidorea) bicolor (Meigen, 1804), Dicranomyia (Dicranomyia) omissinervis de Meijere, 1918, Limonia macrostigma (Schummel, 1829), Tricyphona (Tricyphona) unicolor (Schummel, 1829), and Ula (Ula) bolitophila Loew, 1869.